Enhancing charge separation in conjugated microporous polymers for efficient photocatalytic hydrogen evolution. Issue 22 (28th October 2021) - Qian, Zhuangfei; Yan, Yajie; Liang, Ziqi; Zhuang, Xiaodong; Zhang, Kai A. I.
Abstract : The benzothiadiazole-based conjugated microporous polymer synthesized on graphene via covalent bonds exhibited suppressed charge separation and enhanced photocatalytic hydrogen evolution efficiency. Abstract : The fast recombination of photogenerated electron–hole pairs after charge separation is one of the main factors limiting the achievement of high efficiency of organic semiconductor photocatalysts. Herein, we report a conjugated microporous polymer (CMP)/graphene heterosystem for enhanced photocatalytic hydrogen evolution. Benzothiadiazole-based CMPs were synthesized on graphene sheets Via covalent bonds. Owing to the substantially enhanced charge separation and transfer within the organic semiconductor/conductor heterostructure, the heterosystems exhibited increased photocatalytic hydrogen evolution rates up to 977 μmol g −1 h −1, which is approximately two times as high as that of bulk CMP.